2019
DOI: 10.1039/c9nj01444f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of A-site substitution on the simultaneous catalytic removal of NOx and soot by LaMnO3 perovskites

Abstract: The simultaneous catalytic removal of NOx and soot by La1−xMxMnO3 (M = K, Sr, Pr; x = 0, 0.1, 0.2, 0.3) perovskites was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…In fact, the comparison between NO 2 emission profiles during NO x -TPR experiments (Figure 10) and the corresponding profiles during soot oxidation in NO x -TPR conditions (Figure 12) confirms that the soot oxidation process is carried out by NO 2 reduction, being the difference between profiles the fraction of NO 2 consumed. Finally, as it is expected for manganese-based perovskites [58][59][60], all the catalysts show a high CO 2 selectivity (above 95%) during the NO x -TPR experiment. The electronic configuration of manganese as Mn(III) (d 4 ) is optimal to interact with CO molecules and due to the lability of Mn(IV)-O bond, the CO oxidation is complete at rather low temperatures [49].…”
Section: No X -Assisted Diesel Soot Oxidationsupporting
confidence: 72%
“…In fact, the comparison between NO 2 emission profiles during NO x -TPR experiments (Figure 10) and the corresponding profiles during soot oxidation in NO x -TPR conditions (Figure 12) confirms that the soot oxidation process is carried out by NO 2 reduction, being the difference between profiles the fraction of NO 2 consumed. Finally, as it is expected for manganese-based perovskites [58][59][60], all the catalysts show a high CO 2 selectivity (above 95%) during the NO x -TPR experiment. The electronic configuration of manganese as Mn(III) (d 4 ) is optimal to interact with CO molecules and due to the lability of Mn(IV)-O bond, the CO oxidation is complete at rather low temperatures [49].…”
Section: No X -Assisted Diesel Soot Oxidationsupporting
confidence: 72%
“…In Figure D, the Mn 2p 3/2 and 2p 1/2 peaks for YCMO are positioned at 642.5 and 653.9 eV, respectively, which are consistent not only with the presence of Mn 4+ but also with the coexistence of 2 + oxidation states that have been previously observed for Co . Analogous YNMO samples exhibit comparable peaks, corresponding to Mn 4+ species, which are similar in position, in addition to extra peaks located at 641.7 and 652.9 eV, that can be ascribed to the presence of Mn 3+ ; this set of results implies the presence of mixed oxidation states for both Mn and Ni. Specifically, the pristine YNMO sample consists of a combination of approximately 75% Mn 4+ /Ni 2+ and 25% Mn 3+ /Ni 3+ species.…”
Section: Characterization Of Electrocatalystssupporting
confidence: 84%
“…Perovskite catalysts have received increasing interest over the past decades due to their cost-effective natures, good thermal stabilities, and flexible structures. The outstanding soot catalytic efficiencies of the perovskite-type catalysts have been demonstrated in the literature. , The theoretical studies revealed that B-site components dominate the catalyst performance for the perovskite structure (with general formula ABO 3 ), while A-site elements are critical to the catalyst’s structural behavior and catalytic activity. , Zhao et al investigated the simultaneous removing of NO x and soot over L 1– x M x MnO 3 (M = K, Sr, Pr with x = 0, 0.1, 0.2, 0.3). The K + , Sr 2+ , and Pr 3+ could successfully enter into the lattice that formed perovskite structures.…”
Section: Soot Oxidation Activity Over Manganese Oxide-based Catalystsmentioning
confidence: 99%
“…123,124 The theoretical studies revealed that B-site components dominate the catalyst performance for the perovskite structure (with general formula ABO 3 ), while A-site elements are critical to the catalyst's structural behavior and catalytic activity. 125,126 Zhao et al 96 investigated the simultaneous removing of NO x and soot over L 1−x M x MnO 3 (M = K, Sr, Pr with x = 0, 0.1, 0.2, 0.3). The K + , Sr 2+ , and Pr 3+ could successfully enter into the lattice that formed perovskite structures.…”
Section: Soot Oxidation Activity Over Manganese Oxide-based Catalystsmentioning
confidence: 99%